The filmmaker's handbook : a comprehensive guide for the digital age - Pincus, Edward; Ascher, Steven (New York, New York : Plume, 2012)
"The authoritative guide to producing, directing, shooting, editing, and distributing your video or film. Widely acknowledged as the 'bible' of video and film production, and used in courses around the world, The filmmaker's handbook is now updated with the latest advances in HD and new digital formats. For students and teachers, professionals and novices, this indispensable handbook covers all aspects of moviemaking"--
Introduction to digital and film systems -- Before you begin production -- The video camcorder -- The lens -- The video image -- The film camera -- The film image -- Color and filters -- Shooting the movie -- Sound recording systems -- Sound recording techniques -- Lighting -- Picture and dialogue editing -- Editing digital video -- Sound editing and mixing -- Working with film in postproduction -- Producing and distributing the movie.
Originally published as: The filmmaker's handbook / Edward Pincus and Steven Ascher. 1984.
Includes bibliographical references (pages 791-793) and index.
Keywords: Digital cinematography -- Handbooks, manuals, etc; Digital video -- Handbooks, manuals, etc; Motion pictures -- Production and direction -- Handbooks, manuals, etc; Cinematography -- Handbooks, manuals, etc